Development and Validation of Meta-Learning Assessment Tool (MLAT) to Assess Meta-learning in Secondary Stage Students - Lakshmi, B. M.; Kumar K., Anil (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Meta-learning is encouraged among formal operational stage learners as a key goal of secondary education. The objective is to make students independent learners, who can direct their learning process independently i.e, with minimal guidance by the time they complete their schooling. s. Meta-learning, or "learning to learn," is a crucial skill that enables students to adapt and apply learning strategies effectively in their learning. The assessment of meta-learning becomes crucial to understanding the progress of the implied skills among students. Teachers must adapt strategies that can improve meta-learning in their students, without evaluating which, such improvisations are difficult to achieve. This article focuses on the development and validation of a meta-learning assessment tool, tailored to measure the meta-learning in secondary school students. The process involved establishing a theoretical framework item generation, expert reviews, pilot testing, and comprehensive statistical analyses for validity and reliability. The results indicate that the assessment tool is both reliable and valid, offering a robust tool for educators to measure and enhance meta-learning skills among students.